Efecto de tres abonos orgánicos en el cultivo de fréjol cuarentón (phaseolus vulgaris), en el recinto san Carlos, parroquia Puerto Limón, cantón Santo Domingo provincia de los Tsáchilas - Vargas Vargas, Samuel Yovani (2014)
This work was done at the Finca Mara Bethlehem, located in the San Carlos Campus, Parish Puerto Limon, Santo Domingo Canton Tsáchilas Province. The investigation was designed to assess the crop yield of beans (Phaseolus vulgaris var. Iniap Yunguilla-414), using three types of organic fertilizers at similar doses, considering the following objectives. Beans Increase performance by applying organic fertilizers Bocashi evaluates the effect of pig droppings, manure and cattle, to determine the cost-benefit of each treatment, disseminate the results to the community-based educational material. We implemented the design of randomized complete blocks with their respective comparisons in each of the variables studied. Settling four treatments with four replicates each adding sixteen plots where fertilizers were applied as organic processed: (Bocashi of porquinaza), (Bocashi of manure) and (Bocashi of Beef), using a single dose of each fertilizer treatment 141.44Kg. And finally the witness. The variables were evaluated in each treatment, emergency percentage, days to flowering, plant height at flowering, plant height at harvest, pods per plant, seeds per pod, production per hectare, profitability. We conducted a single application of 0.16 kg from fertilizer (Bocashi), located at the base of the hole at time of planting and replanting the same dose was applied at the base of the plant reaches avoiding contact with the root. To control pests and diseases that attack beans cultivation method was used for prevention, prevention controls was performed using homemade fungicides at different stages of the production phase of the beans. The results were, the effect of treatments on the variable % emergence of seeds, significant differences between means and no difference for replicates, the CV of 4.47 % is good for this type of variable, the average germination of 84.33 % is acceptable. No statistical differences in the variable Days to Bloom, the CV of 7.72 % is acceptable, the average number of days to germination is 34.81. There are statistically significant differences between treatment means in plant height at flowering, no statistical differences between blocks, the CV of 3.09 % is good 5 and average is 27.96 days. In the variable plant height at harvest, pods per plant, grains per pod, Performance and Profitability, mean differences are highly significant, the coefficients of variation are good. The results of the treatments were applied organic fertilizers were much higher compared to the control, being shown that organic fertilizers are necessary for obtaining good help restructure production and soil microorganisms.